Kills Well With Others: Killers of a Certain Age #2 - Raybourn, Deanna (New York : Berkley, 2025)
"Four women assassins, senior in status-and in age-sharpen their knives for another bloody good adventure in this riotous follow-up to the New York Times bestselling sensation Killers of a Certain Age. After more than a year of laying low, Billie, Helen, Mary Alice, and Natalie are called back into action. They have enjoyed their time off, but the lack of excitement is starting to chafe: a professional killer can only take so many watercolor classes and yoga sessions without itching to strangle someone...literally. When they receive a call from the head of the elite assassin organization known as the Museum, they are ready tackle the greatest challenge of their careers. Someone on the inside has compiled a list of important kills committed by Museum agents, connected to a single, shadowy figure, an Eastern European gangster with an iron fist, some serious criminal ambition, and a tendency to kill first and ask questions later. This new nemesis is murdering agents who got in the way of their power hungry plans and the aging quartet of killers is next. Together the foursome embark on a wild ride across the globe on the double mission of rooting out the Museum's mole and hunting down the gangster who seems to know their next move before they make it. Their enemy is unlike any they've faced before, and it will take all their killer experience to get out of this mission alive"--.
new book 2025 spring.
Keywords: Undercover operations; Thrillers Suspense fiction; Female assassins; Assassins; Moles (Spies); Novels; Older women; Webster , Billie (Fictitious character); Tuttle, Mary Alice (Fictitious character); Randolph, Helen (Fictitious character); Schuyler, Natalie (Fictitious character); Novels; Thriller fiction